In response to Ballantyne and Schaefer's 'Consent and the ethical duty to participate in health data research'. Issue 5 (7th January 2019) - Hepgul, Nilay; Sleeman, Katherine E; Firth, Alice M; Johnston, Anna; Teo, James T H; Bernal, William; Dobson, Richard J B; Higginson, Irene J
Abstract : We welcome Ballantyne & Schaefer's discussion of the issues concerning consent and use of health data for research. In response to their acknowledgement of the need for public debate and discussion, we provide evidence from our own public consultation on this topic.